«Si risponde lavorando». Lettere 1941-1992 - Macrí, Oreste (Biblioteca di Studi di Filologia Moderna, 2019)
«Si risponde lavorando». Letters between 1941 and 1992. In 1941, Macrí was a notorious scholar, while Spagnoletti only a debutant poet, but their knowledge of books and magazines brought them to an intense exchange of letters, which would be interrupted in 1956 due to profound disagreements on poetry and on the assessment of Hermeticism. This correspondence, fully transcribed and carefully enriched by Andrea Giusti's notes, retraces that intellectual relationship in some decisive years of Italian history. With Fascism, war and reconstruction as a background, there is the rise of the ferment underlying cultural collaborations, of Spagnoletti's anthologist activity and of Macrí's studies on comparative literature and Spanish, which led him to become more sensitive and open towards European culture.